2021
DOI: 10.5187/jast.2021.e28
|View full text |Cite
|
Sign up to set email alerts
|

Effect of harvest dates on β-carotene content and forage quality of rye (Secale cereale L.) silage and hay

Abstract: Limited data about the effects of various factors on forage quality and β-carotene content of rye produced in Korea are available, so this study investigated the effects of two preservation methods. Samples were collected from rye harvested every 5 days between April 25 and May 31, and comparisons were done among rye silage wilted for different periods of time and hay of three growth stages of rye. For the silage, dry matter (DM), acid detergent fiber (ADF), and neutral detergent fiber (NDF) contents increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
1
13
0
1
Order By: Relevance
“…El índice de Flieg demostró que ensilajes con hasta el 60% de inclusión de maní forrajero presentan excelente cualidad (escore > 81.0) según Dong et al (12). Por otro lado, el ensilaje con el 80% de maní forrajero presentó buena fermentación, con índice de Flieg entre 61-80 (30). Los ensilajes de leguminosas acostumbran a presentar índices de Flieg alrededor de 60,00, caracterizándose cómo ensilajes con preservación comprometida (23).…”
Section: Discussionunclassified
“…El índice de Flieg demostró que ensilajes con hasta el 60% de inclusión de maní forrajero presentan excelente cualidad (escore > 81.0) según Dong et al (12). Por otro lado, el ensilaje con el 80% de maní forrajero presentó buena fermentación, con índice de Flieg entre 61-80 (30). Los ensilajes de leguminosas acostumbran a presentar índices de Flieg alrededor de 60,00, caracterizándose cómo ensilajes con preservación comprometida (23).…”
Section: Discussionunclassified
“…Flieg’s score was calculated from the formula given by Zhang et al [ 15 ]. Lactic acid (LA) was determined by a high performance liquid chromatography (HPLC) system (Agilent HPLC 1260, Agilent Technologies, Santa Clara, CA, US) equipped with a UV detector (column: Agilent Hi-Plex H; mobile phase: 5 mmol/l H 2 SO 4 ; flow rate: 0.7 ml/min; temperature: 55°C); acetic acid (AA), propionic acid (PA) and butyric acid (BA) were measured by gas chromatography (GC), the instrumental conditions were described according to Zhao et al [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Helsel and Thomas (1987) reported greater NDF at dough stage compared with heading and indicated acid detergent fiber (ADF) and NDF were higher in later harvesting dates, while CP was lower as harvesting date was delayed. Zhao et al (2021) reported that as rye maturity increased, total digestible nutrient (TDN), relative feed value (RFV), and CP decreased.…”
Section: Core Ideasmentioning
confidence: 99%